(untitled) (In situ, 2025)
The paper presents the results of archaeological excavations at the Beneficij-Gudulija site near Vela Luka on the island of Korčula, where remains of a Roman rural estate were recorded as early as the mid-20th century. Research in this year is a continuation of those begun in 2018 in cooperation with the Department of Archaeology of the University of Zadar and the Vela Luka Culture Center, which are gradually revealing the spatial and content scope of the site, as well as the dynamics of life in it in the period from the 1st to the 6th century.